Microwave Irradiated Durian Seed Based Activated Carbon For Chloramphenicol Removal - Othman, Siti Aishah (Universiti Sains Malaysia, 2021)
This study aims to synthesis activated carbon (AC) derived from durian seed (DS) to adsorb chloramphenicol (CAP) from an aqueous solution. DSAC was produced via the physical activation method with a continuous flow of carbon dioxide (CO2) gas as an activating agent with microwave irradiation technique. By using response surface methodology (RSM), it was revealed that the optimum preparation conditions of DSAC were 364 W and 6 min for radiation power and radiation time, respectively, which resulted in 50.82% of CAP removal and 45.82% of yield. The adsorption of CAP onto optimized DSAC followed Freundlich isotherm with the adsorption capacities of 1.253, 1.359 and 1.414 at 30°C, 45°C and 60°C respectively. The kinetic studies revealed that the adsorption of CAP onto DSAC followed the pseudo-first order kinetic model while mechanism studies revealed that the adsorption process of CAP onto AC was controlled by the film diffusion mechanism. However, thermodynamic studies confirmed that the studied system was exothermic in nature.